Interdigital lesions and frequency of acute dermatolymphangioadenitis in lymphoedema in a filariasis-endemic area. - Mcpherson, T; Persaud, S; Singh, S; Fay, M; Addiss, D; Nutman, T; Hay, R (2006)
BACKGROUND: Lymphatic filariasis (LF) is a mosquito-borne nematode infection that causes permanent lymphatic dysfunction in virtually all infected individuals and clinical disease in a subset of these. One major sequel of infection is lymphoedema of the limbs. Lymphoedema of the leg affects an estimated 15 million persons in LF-endemic areas worldwide. Acute dermatolymphangioadenitis (ADLA) in people with filarial lymphoedema causes acute morbidity and increasingly severe lymphoedema. Episodes of ADLA are believed to be caused by bacteria, and it has been shown that entry lesions in the skin play a causative role. Clinical observations suggest that interdigital skin lesions of the feet, often assumed to be fungal, may be of particular importance. OBJECTIVES: To investigate the epidemiology and aetiology of interdigital lesions (IDL) of the feet in filarial lymphoedema. METHODS: The frequency and mycological aetiology of IDL in 73 patients with filarial lymphoedema were compared with 74 individuals without lymphoedema in a region of Guyana highly endemic for Wuchereria bancrofti. RESULTS: More than 50% of patients with lymphoedema had one or more IDL (odds ratio 2.69; 95% confidence interval 1.31-5.66; P<0.005 compared with controls). The number of lesions was the strongest predictor of frequency of ADLA. Only 18% of the lesions had positive microscopy or culture for fungi (dermatophytes and Scytalidium). CONCLUSIONS: These findings highlight the importance of interdigital entry lesions as risk factors for episodes of ADLA and have implications for the control of morbidity from filarial lymphoedema.